Daya Penyebaran dan Derajat Kepekaan Sektor Pertanian dalam Pembangunan Ekonomi di Provinsi Jawa Tengah - Rafiqah, Imas Wildan; Darsono, Darsono; Sutrisno, Joko (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Yogyakarta, 2018)
This research aimed to analyze the powerÂ of dispersion and sensitivity of dispersionÂ of the agricultural sector on the economicÂ development of Central Java Province. ThisÂ research used the data of Input and Output Table of Central Java in 2013. DataÂ analysis method applied in this research isÂ Input-Output analysis. The results showedÂ that the agricultural sector represented byÂ the livestock sector had âabove averageâÂ power of dispersion index of the overall index. Livestock sector was able to encourage the production growth in all sectors ofÂ the economy. On the other hand, the sensitivity of dispersion index of all agriculturalÂ sectors was lower than the average valueÂ of the overall index. This reflects the agricultural sectorâs low sensitivity to theÂ changes of the external aspects which results in the low forward linkage among the downstream sectors. In term of keyÂ sector identification, the agricultural sector as a whole was not classified in theÂ priority sector I. However, the livestock subsector, representing the agriculturalÂ sector, was classified in the priority sector II on the economic development ofÂ Central Java Province.